2020
DOI: 10.3389/fchem.2020.00708
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Use of Metal-Organic Frameworks for Dye Adsorption

Abstract: Organic dyes are heavily used in industries for the manufacture of colored goods. This has eventually resulted in the generation of contaminated wastewater which is hard to be purified. Recent studies have demonstrated that metal-organic frameworks (MOFs), a class of supramolecular materials of immense interest, are useful in the adsorption of organic dye molecules because of their modifiable porous structures. In this mini review, the recent advances in the use of MOFs for the adsorption of organic dyes will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…However, the ideal adsorbents not only have high adsorption capacity, but also high adsorption selectivity of the persistent organic pollutants [34,35]. In this context, MOFs are promising alternative adsorbents due to their extraordinary high surface area (up to 7000 m 2 /g [25]), high adsorption capacity, ability to bind various organic pollutant, and adsorption selectivity [7,55,56]. Haque et al shown that MIL-101(Cr) has higher methyl orange (MO) adsorption capacity (114.0 mg/g) than AC (11.2 mg/g), due to surface area of MIL-101(Cr) (3873 m 2 /g) is significantly higher than AC (1068 m 2 /g) [57].…”
Section: Metal-organic Framework As Adsorbentsmentioning
confidence: 99%
“…However, the ideal adsorbents not only have high adsorption capacity, but also high adsorption selectivity of the persistent organic pollutants [34,35]. In this context, MOFs are promising alternative adsorbents due to their extraordinary high surface area (up to 7000 m 2 /g [25]), high adsorption capacity, ability to bind various organic pollutant, and adsorption selectivity [7,55,56]. Haque et al shown that MIL-101(Cr) has higher methyl orange (MO) adsorption capacity (114.0 mg/g) than AC (11.2 mg/g), due to surface area of MIL-101(Cr) (3873 m 2 /g) is significantly higher than AC (1068 m 2 /g) [57].…”
Section: Metal-organic Framework As Adsorbentsmentioning
confidence: 99%
“…MOFs present excellent performance in removing various contaminants from the gaseous and aqueous medium [38]. The most important advantages of MOF over other adsorbents are structural diversity [39], the possibility of determining the size of the pores, as well as determining the properties and performance by selecting various metal nodes and organic ligands in the synthesis stage. Various methods such as solvothermal [40], hydrothermal [41], mechanochemical [42], sonochemical [43], spray drying [44], sol-gel [45], and flow chemistry [46] have been used in MOFs synthesis.…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
“…Interestingly, Fe-HAF-2 sequestered 99% of the cationic dyes (LV + and MB + ) from solution within 10 min, far more rapidly than Fe-HAF-1 and most other reported anionic frameworks. [51][52] To further explore the adsorption kinetics in Fe-HAF-2, the pseudo-second-order model 53 was used to fit the adsorption of MB + over time with different initial concentrations (Figure S15). The linear form of the equation is:…”
Section: Stability Of M-haf-2mentioning
confidence: 99%